Thirty years of standalone percutaneous coronary interventions: A 23, 261 case experience from a Canadian tertiary referral centre. Issue 4 (2015) - Hui, William KK; O´Brien, David G; Brass, Neil S; Cheung, Po Kee; Chan, Michael CY; Leung, Raymond CM; Tyrrell, Benjamin D; Bundhoo, Shantu; Pongnonthachai, Pitak; Galbraith, P Diane; Ranjbar, Keysun; Dorsch, Micha; et al.
No abstract available